Vortioxetine: Clinical Pharmacokinetics and Drug Interactions - Chen, Grace (Clin Pharmacokinet, 2017)
Vortioxetine is a novel antidepressant with multimodal activity currently approved for the treatment of major depressive disorder. Vortioxetine is orally administered once daily at 5- to 20-mg doses. The pharmacokinetics of vortioxetine are linear and dose proportional, with a mean terminal half-life of approximately 66 h and steady-state plasma concentrations generally achieved within 2 weeks of dosing. The mean absolute oral bioavailability of vortioxetine is 75%. No food effect on pharmacokinetics was observed. Vortioxetine is metabolized by cytochrome P450 enzymes and subsequently by uridine diphosphate glucuronosyltransferase. The major metabolite is pharmacologically inactive, and the minor pharmacologically active metabolite is not expected to cross the blood–brain barrier, making the parent compound primarily responsible for in-vivo activity. No clinically relevant differences were observed in vortioxetine exposure by sex, age, race, body size, and renal or hepatic function. Dose adjustment is only recommended for cytochrome P450 2D6 poor metabolizers based on polymorphism of the cytochrome P450 enzymes involved. Similarly, except for bupropion, a strong cytochrome P450 2D6 inhibitor, and rifampin, a broad cytochrome P450 inducer, co-administration of other drugs evaluated did not affect the vortioxetine exposure or safety profile in any clinically meaningful way. Pharmacodynamic studies demonstrated that vortioxetine achieved high levels of serotonin transporter occupancy in relevant brain areas, affected neurotransmitter levels in the cerebrospinal fluid, and modified abnormal resting state networks in the brain over the therapeutic dose range. Overall, vortioxetine can be administered in most populations studied to date without major dose adjustments; however, dose adjustments should be considered on a patient-by-patient basis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40262-017-0612-7) contains supplementary material, which is available to authorized users.